PENGARUH PENGUNGKAPAN GREEN ACCOUNTING DAN CORPORATE GOVERNANCE TERHADAP KINERJA LINGKUNGAN (Studi Empiris pada Perusahaan Energi yang terdaftar di BEI Tahun 2021-2024) - Rossi Mega Aprilia; Widi Hariyanti; Faiz Rahman Siddiq (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the effect of green accounting disclosure and corporate governance on environmental performance of energy companies listed on the Indonesia Stock Exchange during 2021–2024. Environmental performance was proxied by PROPER ratings issued by the Ministry of Environment and Forestry. Using a quantitative approach, this study employed secondary data derived from annual reports and sustainability reports. The sample was selected through purposive sampling, resulting in 25 companies and 93 observations after outlier treatment. Panel data regression with the Random Effect Model was used to test the hypotheses. The results show that recycled material disclosure, corporate social responsibility, and institutional ownership have a positive and significant effect on environmental performance. In contrast, renewable energy disclosure, cost allocation, and the board of commissioners do not have a significant effect, while the audit committee has a significant negative effect. These findings suggest that improving environmental disclosure quality and strengthening institutional monitoring are important to enhance corporate environmental performance. Keywords : green accounting, corporate governance, environmental performance, energy companies, PROPER